The Relationship Between Parental Mediation of Adolescent Media Use and Ugandan Adolescents' Sexual Attitudes and Behavior - Miller, Ann Neville; Gabolya, Charles; Mulwanya, Richard; Nabaseke, Grace; Kiva, Joseph; Nalugya, Evangeline; Lagot, Sarah; Chibita, Monica (Howard Journal of Communications, 2018)
In sub-Saharan Africa, research about the role of media as an influence on adolescent sexual behavior has focused almost exclusively on the effects of health communication campaigns. Little research has explored the association between parents' attempts to guide their children's entertainment media intake, and adolescents' sexual attitudes and behaviors. The authors surveyed 360 Ugandan high school students regarding their parents' mediation of their media use; their attitudes about stereotypical gender roles in sexual relationships and casual sex; and their sexual behaviors. Co-using media with opposite sex friends was associated with higher endorsement of casual sex. Adolescents who reported their parents limited the amount of time they spent with media were less likely to report having ever had sex. However, both effects were smaller than the effects of relationship and demographic variables.
Keywords: parental mediation of media use; sexual media content; Uganda; adolescent media use; sexual debut; sexual attitudes